Pengaruh Edukasi Pencegahan Kekerasan Seksual terhadap Tingkat Kewaspadaan Siswa SDN 010 Batam Kota - Ridni Husnah; Nanda Noor Muhammad Nasution; Miranti Miranti; Fitriani Fitriani (Borneo Nursing Journal (BNJ), 2026)
Sexual violence against elementary school children is a real threat exacerbated by children's low knowledge regarding the boundaries of bodily privacy. This study aims to analyze the effect of providing education on preventing sexual violence on the level of student awareness at SDN 010 Batam Kota. This type of research is quantitative pre-experimental with a One-Group Pretest-Posttest design. The study population included all third-grade students with a sample of 40 students selected using a total sampling technique. Data collection was carried out using a structured questionnaire that measured aspects of good touch and bad touch knowledge as well as students' assertive responses. The data analysis technique used was the Paired Sample T-Test statistical test. The results showed that students' initial level of awareness (pre-test) was in the low category with an average value of 52.4. After being given an intervention in the form of education using audio-visual media and simulation (post-test), students' level of awareness increased significantly to the high category with an average value of 84.1. The results of the statistical test showed a p-value <0.000 (p <0.05), which means H_0 is rejected and H_1 is accepted. The conclusion of this study is that sexual violence prevention education has a significant impact on increasing the awareness of students at SDN 010 Batam Kota. The school is advised to integrate this education into its regular habituation program to maintain student awareness..